Kontekstualisasi Pemikiran Al-Farabi Menuju Indonesia yang Bahagia dan Negara Ideal - syamsiyani yani (Universitas Islam Negeri (UIN) Mataram, 2020)
The political upheaval that has been on display in Indonesia lately is increasingly showing the poor morality of society and the nation's civilization. Al-F?rabi invites politics to achieve the existence of peace and happiness, one of which is the ideal state or al-Madinah al-F?dilah. This is where the goal of presenting the figure of the Islamic philosopher, al-F?rabi as a very famous figure who is famous for his thought ‘ara Ahl al-M?dinah. The method used in this research is a descriptive qualitative library research approach. A descriptive approach is a research method that aims to develop a theory of thought or figure. The aim is to reveal the reality of al-F?rabi's thinking in accordance with the reality in the field, from al-F?rabi's political thinking is expected to create an advanced Indonesian state, a happy and ideal country, especially for universal community life.